2013
DOI: 10.1016/j.janxdis.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and parenting predicting anxiety change in cognitive behavioral therapy: The role of mothers, fathers, and children

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim. t r a c tObjective: A considerable amount of children with anxiety disorders do not benefit sufficiently from cognitive behavioral treatment. The present study examines the predictive role of child temperament, parent temperament and parenting style in the context of treatment outcome. Method: Participants were 145 children and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 50 publications
2
12
0
Order By: Relevance
“…Treatment was associated with fewer anxiety disorders 1 year after the intervention, suggesting that parents can successfully reduce anxiety symptoms in children, given appropriate support. However, studies have also demonstrated that maternal anxiety, negative affect, and low emotional warmth predict poorer child responses to anxiety treatments [Festen et al, ; Hudson et al, ]. Parenting stress may also hinder treatments contingent on parent‐child interactions, as higher levels of parenting stress are associated with fewer parent‐child interactions in families affected by FXS [Wheeler et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment was associated with fewer anxiety disorders 1 year after the intervention, suggesting that parents can successfully reduce anxiety symptoms in children, given appropriate support. However, studies have also demonstrated that maternal anxiety, negative affect, and low emotional warmth predict poorer child responses to anxiety treatments [Festen et al, ; Hudson et al, ]. Parenting stress may also hinder treatments contingent on parent‐child interactions, as higher levels of parenting stress are associated with fewer parent‐child interactions in families affected by FXS [Wheeler et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Festen and colleagues (2013) showed that children seeking treatment for anxiety disorders were more responsive when they were reported to have higher initial manifestations of surgency. Person-centered patterns of temperament—considering the ways groups of children with different dispositional patterns across multiple temperament factors vary in outcomes—have also shown implications for child psychopathology.…”
Section: Temperamentmentioning
confidence: 98%
“…Despite the considerable literature base on temperament influences within ADs, few studies have examined specific patterns of temperament in youth with SP or how patterns of temperament may promote or hinder treatment and clinical outcomes in such youth. Understanding these patterns might clarify an important contributor to different patterns of treatment response for SP (Festen et al, 2013; Ollendick & Davis, 2013). Although OST is an effective treatment for SPs, as noted earlier, a subset of children with SPs do not respond to OST.…”
Section: Temperamentmentioning
confidence: 99%
“…It appears that gender and several personality characteristics (extraversion) can influence online counseling, help-seeking [43]. Parental behaviors and parental cognitions have also been related to CBT outcomes [44,45], with CBT treatment for anxious youth successfully changing parent-related variables (parenting, cognitions). Family accommodation for anxiety, defined as the involvement of parents in an anxious youth's efforts to avoid anxiety-provoking activities/situations, is another important factor that should be considered.…”
Section: Parental Factorsmentioning
confidence: 99%